Effects of Homogenization Heat Treatment on Microstructure of Inconel 718 Lattice Structures Manufactured by Selective Laser Melting - Chicos, Lucia-Antoneta; Lancea, Camil; Zaharia, Sebastian-Marian; Cempura, Grzegorz; Kruk, Adam; Pop, Mihai Alin (MDPI AG, 2025)
Inconel 718 is a nickel-based superalloy that has a wide range of applications in the industries that require corrosion resistance or high-temperature resistance. It is well known that parts display internal stresses, anisotropy, and alloying element segregation after the selective laser melting (SLM) process. A homogenization heat treatment, which reduces internal stresses and homogenizes the material structure, can resolve these shortcomings. The present study focuses on the impact of this heat treatment on the microstructure of the Inconel 718 material produced by SLM. The research results indicate that this heat treatment improves both the material microstructure and mechanical performance by lessening the microstructural inhomogeneities, dissolving the Laves phases, and promoting grain coarsening. The findings of this study can contribute to the optimization of postfabrication strategies for Inconel 718 parts fabricated by SLM.
Keywords: Inconel 718; homogenization heat treatment; microstructure; selective laser melting; Laves phase; δ phase; γ’ and γ” phases; post-fabrication optimization